Implikasi Kriteria Neo-Mabims Pada Penentuan 1 Dzulhijjah 1443 H (Studi Kritis Konsep Matla’ dalam Hadis) - Hijriyati, Muthiah; Islam, Ahmad Fakhruddin Fajrul (Azimuth: Journal of Islamic Astronomy, 2023)
Abstract:        Mabims criteria that have been implemented in Indonesia since Ramadan 1443 Hijriyah have become a new discourse. The criteria for the minimum height of the hilal of  3 degrees and elongation of 6.4 degrees annul the previous criteria, namely the minimum height of the hilal of 2 degrees, elongation of 3 degrees and hilal mucus for 8 hours. This change became a new problem considering that on 29 Dhulqa'dah 1443 H all regions in Indonesia had not yet reached the latest Imkanur rukyah MABIMS criteria. Therefore, this research was conducted aiming to find out the implications of the latest MABIMS criteria on the determination of 1 Dhulhijjah 1443 H with the analysis of Ma'anil Hadith related to Matla' as the theoretical basis used. Using qualitative research methods with data collection by library research. This data is both primary and secondary to be analyzed by interconnecting the theory of ma'anil hadith with the conception of the visibility of the new moon in the latest MABIMS criteria. The results of this study illustrate that the difference in matla' has emerged since the time of the Companions as in the hadith narrated by Kuraib and this becomes the basis for the possibility of different days for certain regions on Earth, as in Saudi Arabia which performs wukuf in Arafah and Eid al-Adha is different from in Indonesia. Of course this is not the first time in Indonesia, but potential conflicts and theoretical weaknesses must be resolved for the common good. Keywords:      Neo-Mabims Criteria, Matla', Ma'anil Hadith   Abstrak:         Kriteria MABIMS yang telah diterapkan di Indonesia sejak Ramadhan 1443 Hijriyah menjadi wacana baru. Kriteria dengan tinggi hilal minimal 3 derajat dan elongasi 6,4 derajat, merubah kriteria sebelumnya yaitu tinggi hilal minimal 2 derajat, elongasi 3 derajat dan umur hilal 8 jam. Perubahan ini menjadi masalah baru mengingat pada tanggal 29 Dzulqa'dah 1443 H seluruh wilayah di Indonesia belum mencapai kriteria MABIMS Imkanur Rukyah Baru. Oleh karena itu, penelitian ini dilakukan dengan tujuan untuk mengetahui implikasi kriteria Neo-MABIMS Baru terhadap penentuan 1 Dzulhijjah 1443 H dengan analisis Ma'anil Hadits terkait Matla' sebagai dasar teori yang digunakan. Penelitian ini menggunakan metode penelitian kualitatif dengan pengumpulan data berupa studi pustaka. Data ini bersifat primer dan sekunder untuk dianalisis dengan menghubungkan teori ma'anil hadits dengan konsepsi visibilitas hilal dalam kriteria Neo-MABIMS. Hasil penelitian ini menggambarkan bahwa perbedaan matla' telah muncul sejak zaman para sahabat seperti dalam hadits yang diriwayatkan oleh Kuraib dan ini menjadi dasar kemungkinan hari yang berbeda untuk wilayah tertentu di Bumi, seperti di Arab Saudi yang melakukan wukuf di Arafah dan Idul Adha berbeda dengan di Indonesia. Tentu ini bukan pertama kalinya di Indonesia, tetapi potensi konflik dan kelemahan teoritis harus diselesaikan untuk kebaikan bersama. Kata Kunci:   Kriteria Neo-Mabims, Matla’, Ma’anil Hadis